Underlying Dimensions of Purchase Decision Process for Consumer Durables: A Confirmation of the Customer - Value Hierarchy Model - Matai, Rajesh; Bhat, Anil K. (Indian Journal of Marketing, 2012)
The purpose of this study was to find out the dimensions (factors) that customers use in deciding about purchasing a consumer durable, more specifically, a color television. A thirteen item questionnaire was used to elicit responses from 100 potential customers in the city of Jaipur. Factor analysis (data reduction technique) was applied on the collected data. It resulted in the emergence of five factors viz. Core Features; Reliability and Cost; Ease of Operation; Memory, Aesthetic, and Response features; Brand Performance and New features. This seems to confirm the customer - value hierarchy model of five product levels namely Core Benefit, Basic Product, Expected Product, Augmented Product, and Potential Product as these levels match with the earlier five factors presented in the research study. The implication of this study is the continued relevance of looking at a consumer durable as a five layered product offering.